Indian Banking Industry Comparative Performance Evaluation in the Liberalized and Globalized Era - uppal, RK; Kaur, Rimpi (Gyan Management Journal, 2007)
commercial banks and further examined the factors responsible for the changes. The paper concludes that the public sector banks have dominant position in their share in total assets of all scheduled commercial banks i.e. 72 pc and new private sector banks are following with 15 pc share. Among all the factors under study, profitability have recorded deterioration in all the bank groups during the study period as public sector banks witnessed the least profitability i.e. 0.82 pc along with the highest costs and decreasing spread even succeeded to bring down their non-performing assets and intermediation cost.
Keywords: lberalization and Globalization; Structure of Indian Banks; Performance Evaluation; Implications and Issues of Future Research